Participating mortgages and the efficiency of financial intermediation - Ebrahim, M. Shahid; Shackleton, Mark B.; Wojakowski, Rafał M. (Journal of Banking & Finance, 2011)
This paper establishes a basic framework to study three different variants of Participating Mortgages (PMs). We obtain results for Shared Appreciation Mortgages (SAMs), Shared Income Mortgages (SIMs) and Shared Equity Mortgages (SEMs) in closed-form. We illustrate our findings with examples that show PMs are also attractive in an environment where prepayment can occur. Finally we conclude with the public policy implications of employing PMs as workout loans, especially post sub-prime crisis. We argue that by facilitating better risk sharing, PMs offer a means to enhance the efficiency and resiliency of the financial system.